Multifactorial assessment and targeted intervention for preventing falls and injuries among older people in community and emergency care settings: systematic review and meta-analysis. - Gates, S; Fisher, J; Cooke, M; Carter, Y; Lamb, S (2008)
OBJECTIVE: To evaluate the effectiveness of multifactorial assessment and intervention programmes to prevent falls and injuries among older adults recruited to trials in primary care, community, or emergency care settings. DESIGN: Systematic review of randomised and quasi-randomised controlled trials, and meta-analysis. DATA SOURCES: Six electronic databases (Medline, Embase, CENTRAL, CINAHL, PsycINFO, Social Science Citation Index) to 22 March 2007, reference lists of included studies, and previous reviews. REVIEW METHODS: Eligible studies were randomised or quasi-randomised trials that evaluated interventions to prevent falls that were based in emergency departments, primary care, or the community that assessed multiple risk factors for falling and provided or arranged for treatments to address these risk factors. DATA EXTRACTION: Outcomes were number of fallers, fall related injuries, fall rate, death, admission to hospital, contacts with health services, move to institutional care, physical activity, and quality of life. Methodological quality assessment included allocation concealment, blinding, losses and exclusions, intention to treat analysis, and reliability of outcome measurement. RESULTS: 19 studies, of variable methodological quality, were included. The combined risk ratio for the number of fallers during follow-up among 18 trials was 0.91 (95% confidence interval 0.82 to 1.02) and for fall related injuries (eight trials) was 0.90 (0.68 to 1.20). No differences were found in admissions to hospital, emergency department attendance, death, or move to institutional care. Subgroup analyses found no evidence of different effects between interventions in different locations, populations selected for high risk of falls or unselected, and multidisciplinary teams including a doctor, but interventions that actively provide treatments may be more effective than those that provide only knowledge and referral. CONCLUSIONS: Evidence that multifactorial fall prevention programmes in primary care, community, or emergency care settings are effective in reducing the number of fallers or fall related injuries is limited. Data were insufficient to assess fall and injury rates.